Moderate to high ethanol and acetaldehyde administration decreases c-fos protein expression in the hippocampus of Aldh2-knockout and C57BL/6N mice (Bangladesh Journal of Medical Science, 2019)
Background: Ethanol (EtOH) and acetaldehyde (AcH) have long been associated with many adverse effects in the central nervous system. c-fos has been used as an indirect index of neural activity.Method: Here, we investigated the effects of systemic administration of EtOH and AcH on the expression of c-fos protein in the hippocampus of Aldh2-knockout (Aldh2-KO) mice. The animals received an intraperitoneal injection of saline (control), EtOH (1.0, 2.0 and 4.0 g/kg) or AcH (50, 100 and 200 mg/kg), and the expression of c-fos protein was measured by Western blotting.Result: We found that EtOH at doses of 2.0 and 4.0 g/kg decreased c-fos in wild-type (WT) mice, whereas EtOH at all three doses tested (1.0-4.0 g/kg) decreased c-fos in Aldh 2-KO mice. Likewise, AcH at doses of 100 and 200 mg/kg had a significant effect in lowering c-fos protein in both WT and Aldh2-KO mice.Conclusion: Our observations suggest that moderate to high EtOH and AcH can decrease the expression of c-fos protein in the mouse hippocampus. This effect may support, at least in part, the link between c-fos and spatial memory deficits following EtOH and AcH exposure as we have observed in our previous study.Bangladesh Journal of Medical Science Vol.19(1) 2020 p.83-89